Perbandingan Kuat Tekan Beton Menggunakan Campuran Sirtu Terhadap Beton Normal - Gustina, Gustina; Renjani, Muhammad Sodri; Nasatian, Ari Endra; Kutni, Darul; Rianto, Doli Jumat (Jurnal Talenta Sipil, 2025)
The existence of sirtu in the open air is the main choice, it is easy to find, but sometimes it is not known what the ideal percentage is needed to add sirtu as an additional mixture in making concrete according to the desired concrete quality. This type of research is quantitative research with an experimental method to determine the comparison of the compressive strength of concrete with the addition sand and stone in the concrete mixture against normal concrete. A sample of 27 test specimens with concrete age tolerance testing carried out at the ages of 7, 14 and 28 days. The comparison of optimum concrete compressive strength will be seen on the 28th day using a compressive strength test tool in the form of a hammer test and compression testing machine. The test results using the hammert test tool on normal concrete samples were 251.23 kg/cm2, the addition of 25% sirtu obtained 225.50 kg/cm2 and the addition of 50% sirtu obtained a compressive strength test of 221.86 kg/cm2. Meanwhile, testing with a compression testing machine on normal concrete samples obtained 278.04 kg/cm2, adding 25% sirtu obtained 273.51 kg/cm2 and adding 50% sirtu obtained a compressive strength test of 242.44 kg/cm2. Overall, the concrete compressive strength test tool for the variables used showed a decrease in the results of the normal concrete compressive strength test along with the addition of the percentage of sirtu, but still in accordance with the quality standards of the concrete produced above 20 MPa which was measured on days 7, 14, and 28. Overall, the concrete compressive strength test tool for the variables used shows a decrease in the results of the normal concrete compressive strength test along with the addition of the percentage of sirtu, meaning that the higher the percentage of sirtu used, the lower the compressive strength of the concrete produced along with the increasing age of the concrete, but still in accordance with the quality standards of the concrete produced above 20 MPa which is measured on the 7th (seventh), 14th (fourteenth), and 28th (twenty-eighth) days.